PENGARUH PERAN KELUARGA, PETUGAS KESEHATAN DAN MEDIA SEBAGAI SUMBER INFORMASI TERHADAP PENGETAHUAN LARANGAN MEROKOK DALAM RUMAH DI DESA UJUNGGEBANG KECAMATAN SUKRA TAHUN 2019 - Depi Yulyanti; Bayu Sela Priyatna; Geby Dhea Lukita (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Smoking behavior in the Ujung Gebang Village community home is more than 50%, of the 200 households monitored by 74.5% smoking inside the house. The purpose of this study was to determine the effect of the role of family, health workers and the media as a source of information on knowledge of smoking bans in homes in Ujunggebang Village. The research uses survey method with Cross Sectional approach. The population of the study was 1321 heads of households, the determination of the sample was using the Slovin formula of 93 heads of households, the sampling technique used accidental sampling using a questionnaire, statistical tests using the Chi-Square Test. The results showed there was an influence between the role of family on knowledge with a value of p = 0.007, there was no effect between the role of health workers on knowledge with a value of p = 0.105, and there was no influence between the role of the media on knowledge with a value of p = 0.098. family role. So family members must be educated about the dangers of smoking and prohibit smoking in the house